IMPROVING THE REGULATION AND INCENTIVE FEATURES OF PERSONAL INCOME TAXATION (American Journal of Business Management, Economics and Banking, 2025)
This article provides relevant proposals and recommendations for further improving the regulation and incentive mechanisms of personal income taxation in Uzbekistan, based on a study of international experience in taxing individual incomes.